Application Of Tourist Route Map Based On Modification Bidirectional A * Algorithm - Panji Winata; - Wijanarto (Universitas Dian Nuswantoro and IndoCEISS, 2017)
Tourism is an activity that has become a trend of human needs. The development of technology in the current era is very helpful in providing such information to tourists, one of which is information about the route in the planning of tourism activities. Tourists will certainly choose the optimal route in their journey to make their tours more effective. In order to determine the fastest route, this paper will present a mobile-based application that will help tourists to quickly reach the destination. The Efficient Modified Bidirectional A * algorithm is chosen because it will provide an efficient route with shorter distance, which is a modification of the A * algorithm. The results of the case study of 5 trips from the starting point toward the goal resulted in a high level of efficiency (3 cases) and quite good (3 cases) with values, 77.5%, 53%, 53.8%, 73%, 72.6 %. The above percentage is calculated by finding a proportional distance (d) of choice with the distance of all possible paths, then subtracting 1 by multiplying d by 100%. In the future work need to add the parameters of the busy road route or not to be selected more optimal.